Molecular modelling of HLA‐B*35:132. (9th January 2014) - Longhi, E.; Crivello, P.; Mantovani, M.; Frison, S.; Fleischhauer, K.; Crespiatico, L.; Piccolo, G.; Poli, F.
Summary Here we describe the molecular modelling of the new variant HLA‐B*35:132. This allele shows one mismatch with B*35:01:01:01 in exon 3 at position 575 where a T is substituted by a C, which implies an amino acidic change from Leucine to Proline. This seems not to alter the molecular structure and not to compromise the HLA complex and T‐cell receptor interaction.